2015
DOI: 10.1007/s11249-015-0520-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Friction and Wear Reduction by Carbon Fiber Reinforcement of PEEK

Abstract: Carbon fibers are widely used as reinforcements in poly-ether-ether-ketone (PEEK). In recent years, these materials have also been used for tribological applications. For further optimization of these tribo-materials, the contribution and action mechanisms of carbon fiber reinforcements to the tribological performance of PEEK composites need to be understood. Toward this goal, we have studied carbon fibers in a PEEK composite by scratching experiments using Berkovich and conical indenters and friction imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Because of the high strength and shear modulus of carbon fibers, the applied load is born mostly by carbon fibers in the composite; as a result, the friction behavior of the composites is significantly characterized by carbon fibers [9,44]. In addition, since carbon fibers are well-known as a solid lubricant [45], the tribological properties are enhanced in the presence of carbon fibers on contact surfaces.…”
Section: Tribological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high strength and shear modulus of carbon fibers, the applied load is born mostly by carbon fibers in the composite; as a result, the friction behavior of the composites is significantly characterized by carbon fibers [9,44]. In addition, since carbon fibers are well-known as a solid lubricant [45], the tribological properties are enhanced in the presence of carbon fibers on contact surfaces.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5][6] because of lightweight, high strength and stiffness [7], corrosion resistance [8], and low friction coefficient [9]. Growing world demand for using more environment friendly materials has resulted in a push for using bio-based materials in polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…While there are many attempts to improve the tribological performance of PEEK from the material side, as in the case of PEEK composites with specific fillers [24][25][26][27][28][29], fluid lubrication has the potential to further reduce friction and wear of PEEK. Zhang et al [30] reported lubrication with diesel fuel decreased friction and wear of PEEK in a PEEK plate/steel ring sliding contact while observing the transfer film on steel counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have been performed to study the tribological performance of CF reinforced PEEK composites. They found that the addition of CF can greatly improve the wear resistance of PEEK under different applied conditions such as sea water lubrication, water lubrication, and dry sliding wear . As an important solid lubricant, PTFE has been widely used in chemical processing, spacecraft design, and biotechnology industries due to its attractive physical and chemical properties, such as low frictional coefficient, good thermal, and chemical stability .…”
Section: Introductionmentioning
confidence: 99%